Occurrence of Rhabdochona fortunatowi Dinnik, 1933 (Nematoda: Rhabdochonidae) in Two Endemic Cyprinid Species (Capoeta spp.) in Turkey - Aydoğdu, Ali; Emre, Yılmaz; Emre, Nesrin; Yabacı, Ayşegül; YABACI TAK, AYŞEGÜL (My University, 2021)
Two endemic freshwater cyprinid fishes, Capoeta caelestis Schöter, Özuluğ & Freyhof, 2009 and C. angorae (Hankó, 1925), have been studied for the presence of parasitic nematodes in Fırnız Stream, K. Maraş, Göksu River, Antalya, in the Anatolian Region of Turkey. Only a species of the genus Rhabdochona was found in intestines and identified as R. fortunatowi Dinnik, 1933. Totally, 104 specimens of R. fortunatowi infected 19 out of 99 individuals of C. caelestis (prevalence 19.1 %, mean intensity 5.4). In C. angorae, 40 specimens of R. fortunatowi infected 15 out of 178 fish individuals (prevalence 8.4 %, mean abundance 2.6). Prevalence and intensity of R. fortunatowi infection were calculated across the seasons as well as in age groups and sexes of hosts. The present study provides the first record of R. fortunatowi in Turkey and the first host records of this parasite in both C. caelestis and C. angorae, thus expanding the known geographical and host range of this nematode species.